2022
DOI: 10.1093/eurpub/ckac130.140
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in higher education students: findings from a Portuguese study

Abstract: Background Health literacy (HL) concerns the knowledge and competences of people to meet the complex demands of health in modern society. It is essential for health promotion, disease prevention and healthcare. Young adults can perform a very important role in taking a more active role in managing and protect their health, so this study aimed to identify the HL levels in the population of higher education students, according to the European Health Literacy Survey (HLS-EU-PT) and to evaluate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Hal ini dimungkinkan karena fakultas kesehatan lebih banyak terpapar informasi -informasi kesehatan, baik dari kurikulum pelajaran, pelatihan ataupun seminar yang mereka ikuti (40). Pada penelitian terhadap mahasiswa di Portugis, mengungkapkan bahwa literasi kesehatan cenderung cukup atau sangat baik diantara mahasiswa dari jurusan terkait kesehatan (41). Mahasiswa psikologi dan kedokteran menunjukkan tingkat literasi kesehatan mental yang lebih tinggi, dibandingkan dengan mahasiswa dari bidang ilmu alam, ekonomi, dan hukum (42).…”
Section: Pembahasanunclassified
“…Hal ini dimungkinkan karena fakultas kesehatan lebih banyak terpapar informasi -informasi kesehatan, baik dari kurikulum pelajaran, pelatihan ataupun seminar yang mereka ikuti (40). Pada penelitian terhadap mahasiswa di Portugis, mengungkapkan bahwa literasi kesehatan cenderung cukup atau sangat baik diantara mahasiswa dari jurusan terkait kesehatan (41). Mahasiswa psikologi dan kedokteran menunjukkan tingkat literasi kesehatan mental yang lebih tinggi, dibandingkan dengan mahasiswa dari bidang ilmu alam, ekonomi, dan hukum (42).…”
Section: Pembahasanunclassified
“…According to research, higher education students exhibit lower levels of health literacy compared to other students of the same age [14]. For instance, a study conducted on Portuguese students found that 44% of them had problematic or inadequate health literacy levels [15]. University is a crucial transitional period for many students, as they move from adolescence to young adulthood and become more independent in making healthrelated decisions [16].…”
Section: Introductionmentioning
confidence: 99%